2016
DOI: 10.1364/ol.41.004983
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast creation and control of population density gratings via ultraslow polarization waves

Abstract: In the regime of resonant coherent light-matter interaction, light pulses may interact with each other indirectly via a polarization wave created by the other pulse. We show that such interaction allows fast creation and erasing of high-contrast dynamic population density gratings, as well as control of their period in a few-cycle regime. Our scheme uses counter-propagating optical pulses, which do not cross each other in the medium. The mechanism is able to work with pulse durations up to the single-cycle lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
54
0
24

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(86 citation statements)
references
References 31 publications
8
54
0
24
Order By: Relevance
“…Therefore, it seems to be of great interest to investigate optical response of the disordered media when the light frequency is close to the frequency of atomic resonance. This proximity to the resonance results in a bunch of nonlinear optical effects such as self-induced transparency (SIT) [16,17], optical bistability [18,19], optical kinks [20,21], unipolar pulse generation [22], population density gratings formation [23,24], etc. However, resonant nonlinearities are rarely considered in the literature on disordered photonics.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it seems to be of great interest to investigate optical response of the disordered media when the light frequency is close to the frequency of atomic resonance. This proximity to the resonance results in a bunch of nonlinear optical effects such as self-induced transparency (SIT) [16,17], optical bistability [18,19], optical kinks [20,21], unipolar pulse generation [22], population density gratings formation [23,24], etc. However, resonant nonlinearities are rarely considered in the literature on disordered photonics.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we revise recently proposed [7][8][9][10][11] novel method of creation and ultrafast control of spatial periodic gratings of polarization and inversion by few-cycle pulses coherently propagating in a resonant medium. This method allows achieving the subwavelength gratings by the pulses nonoverlapping in space, which is contrast to well-known method, where overlapping of the pulses is needed [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Using of unipolar subcycle pulses (6) seems to have more advantages with respect of bipolar ones (6) seems to have more advantages due to their smaller duration and unipolar character. Numerical simulations revealed that with proper selection of the delay between the incident bipolar few-cycle bipolar pulses (5) of subcycle pulses (6) and their propagation directions it is possible to create, erase and even multiplicate the spatial period of polarization and inversion gratings, see [7][8][9][10]. Figure 1 illustrates the typical dynamics of inversion n under the action of single-cycle bipolar pulse train (5).…”
mentioning
confidence: 99%
“…Такой 2π-импульс СИП распространяется в резонансной среде без потерь. Использование СИП открывает новые возможности в генерации ПКИ им-пульсов аттосекундной длительности в резонансных сре-дах [17][18][19][20][21][22][23][24][25][26][27][28], возможность наведения в среде решеток инверсии и сверхбыстрого управления ими с помо-щью последовательности ПКИ, не перекрывающихся в среде [29][30][31][32][33].Основным понятием, широко применяемым при опи-сании когерентных резонансных взаимодействий корот-ких импульсов с веществом, является понятие площади импульса(d 12 -дипольный момент перехода, ε(t) -медлен-ная огибающая импульса) [13][14][15][16]. Эволюция площади импульса при когерентном распространении длинных импульсов в резонансных средах подчиняется теоре-ме площадей Мак-Колла и Хана [13][14][15][16].…”
unclassified